Comparative Characteristics of Corneal Confocal Microscopy after UV-A Cross-linking with Different Riboflavin Solutions in Experiment - M. M. Bikbov; A. R. Khalimov; E. L. Usubov; G. Kh. Zainutdinova; I. D. Valishin; L. I. Gilemzyanova (Oftalʹmologiâ, 2024)
Corneal cross-linking (CXL) has become the most common way of managing keratectasia. To date, the Dresden protocol (G. Wollensak et al., 2003) has acquired many modifications, in which the composition of the applied agents or modes of CXL procedure have been changed. This article presents the results of studying morphological changes of rabbit cornea in vivo after CXL using riboflavin solutions of different composition.Purpose: compare the effect of CXL on the corneal morphological structure in experimental animals by confocal microscopy using riboflavin with saline, dextran and hydroxypropylmethylcellulose.Material and methods. The study was performed on 20 eyes of 15 rabbits, which underwent standard (Epi-Off) CXL with 0.1 % riboflavin in 3 groups: in the first group saline was used as a base, in the second group — 20 % dextran, in the third — 1.0 % hydroxypropyl methylcellulose (HPMC). Corneal irradiation mode: 3 mW/cm2, 30 minutes, wavelength 370 nm. The corneal condition was evaluated at 3, 7, 14, 30 and 90 days after CXL. Biomicroscopy and confocal microscopy were performed in all animals using Heidelberg Retinal Tomographer HRT-III (Heidelberg Engineering, Germany). Keratocyte density was counted at the depth of 120–160 μm in the central zone on the area of 1 mm2. Statistical processing of the results was performed using Statistica 6.1 and Excel 2010 programmes.Results. In vivo biomicroscopy and confocal microscopy of the rabbit corneas showed postoperative changes in the epithelium and stroma after CXL. In all groups, 7 days after CXL, there was a decrease in keratocyte density, due to apoptosis, observed predominantly in the anterior layers of the stroma. The number of keratocytes after CXL in group 1 was 192.5 ± 29.8 cells/mm2, in group 2 — 227.4 ± 38.2 cells/mm2, in group 3 — 204.4 ± 32.6 cells/mm2 against intact control 352.8 ± 35.2 cells/mm2. There was not statistically significant difference between the groups.Conclusion. The results of lifetime confocal microscopy of the rabbit cornea demonstrated similar morphological changes in the early postoperative period, which were accompanied by the loss of subepithelial nerve fibres, development of lacunar edema, apoptosis of keratocytes with a decrease in their density mainly in the anterior and middle layers of the stroma. The beginning of keratocyte repopulation and nerve fibre regeneration was observed on the 30th day after CXL. No signs of endothelium damage were detected. A comparative assessment of the greatest effectiveness of CXL techniques with 0.1% riboflavin in saline, dextran or HPMC can be given on the basis of larger-scale experimental and clinical studies.